Analisis Determinan Kepatuhan Menjalani Hemodialisa Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik - Riris Andriati; Aisyah Aisyah (Edu Masda Journal, 2021)
In 2015, the number of cases of end stage chronic kidney failure in Indonesia was 70 thousand sufferers. Based on these figures, patients undergoing hemodialysis therapy are only 4000 to 5000 patients with renal failure. The objective of this study was to determine the relationship between adherence to hemodialysis therapy and the quality of life of patients with chronic renal failure in the Hemodialysis Unit of Haji Hospital Jakarta. This research method is a quantitative study with a cross-sectional design. The number of samples was 54 people who were in the hemodialysis unit of the Jakarta Hajj Hospital during the last three months. The results of the study Respondents with good quality of life, moderate compliance were 1 respondent (%), and good quality were 10 respondents (%). The results of bivariate analysis using the Chi Square test, obtained p value = 0.468˃0.05. This means that there is no relationship between compliance undergoing hemodialysis with the quality of life of patients at the Jakarta Hajj Hospital.